Drug Prevention of Reperfusion Lesions during Thrombolytic Therapy for Myocardial Infarction - G. A. Boyarinov; A. A. Usanova; I. S. Kotlov; A. S. Saushev; A. P. Komkov (Общая реаниматология)
Objective: to evaluate the efficacy of mexicor used to protect cardiac metabolism in patients with myocardial infarction during thrombolytic therapy with streptokinase. Subjects and methods. Fifty-four patients (mean age 51.2±5.5 years) with myocardial infarction, who underwent thrombolytic therapy with streptokinase from 30 minutes to 2 hours after the onset of the disease, were examined and cured. During the basic treatment, 28 patients received the mexicor regimen: 5—6 mg/kg intravenously before thrombolysis, then 50 mg/day as continuous infusions for 3 days with its further use as 200-mg capsules thrice daily until they were discharged from hospital. The time course of changes in £ST, the parameters of cardiac hemodynamics, systemic circulation, the activities of creatine phosphokinase-MB and malondi-aldehyde, and the values of the antioxidant system were analyzed during and after thrombolysis. Results. It was established that after administration of mexicor, the patients showed a less pronounced tendency for hypodynamic circulation and postinfarction left ventricular dilatation at the thrombolytic stages and in the postperfusion period. The frequency of high-grade reperfusion arrhythmias (after B. Lown) was 2.18-fold less and the rate of ST-segment isoelectric line achievement was higher. During hospital mexicor treatment, the frequency of heart failure and postinfarct angina pectoris episodes was decreased from 30.8 to 17.7% and from 19.2 to 10.7%, respectively; recurrent infarctions occurred 2.68-fold less frequently. Conclusion. The use of mexicor during thrombolytic therapy for myocardial infarction promotes cardiac metabolic protection during and after thrombolysis. Administration of mexicor results in a more complete recovery of cardiovascular function, cardiac hemodynamics, and metabolism in patients after thrombolysis and favors a reduction in the number of disease complications in the hospital treatment stage. Key words: myocardial infarction, thrombolysis, reperfusion, mexicor, streptokinase.